2005
DOI: 10.1007/s11095-005-7415-5
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the P-Glycoprotein Dependent Pharmacokinetics of Digoxin in Rats by Human Recombinant Interferon-α

Abstract: IFN-alpha induces in vivo a significant dose-dependent inhibitory effect on intestinal P-gp activity related to a local decrease in its expression, thereby predicting important clinical consequences when IFN-alpha and other P-gp substrates are associated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Therefore, the direct influence of EFV on P-gp function was examined at the BBB. Results showed that EFV did not alter the rat brain concentration of digoxin, a P-gp substrate (27). This was confirmed on GPNT cells, in which digoxin uptake remained unchanged with EFV.…”
Section: Discussionmentioning
confidence: 61%
“…Therefore, the direct influence of EFV on P-gp function was examined at the BBB. Results showed that EFV did not alter the rat brain concentration of digoxin, a P-gp substrate (27). This was confirmed on GPNT cells, in which digoxin uptake remained unchanged with EFV.…”
Section: Discussionmentioning
confidence: 61%
“…The concept of anatomical region-dependant modification of P-gp was already proposed to account for the inhibiting effect of some drugs on intestinal P-gp. For instance, IFN-α substantially inhibits P-glycoprotein expression in rats jejunum and ileum [26]. Quinidine increases ileal and jejunal digoxin absorption by inhibiting P-gp in rats [27].…”
Section: -Discussionmentioning
confidence: 99%
“…Ben Reguiga et al (2005) have studies the effect of IFN-α on the pharmacokinetics of two different P-gp substrates in rats, namely digoxin and docetaxel. IFN-α given daily for 8 days to rats, was found to have a dose-dependent inhibitory effect on intestinal P-gp activity.…”
Section: Drug Interaction With Therapeutic Proteinsmentioning
confidence: 99%